Review of Penelope Buckley's The Alexiad of Anna Komnene: Artistic Strategy in the Making of a Myth - Linardou, Kallirroe (Historein, 2015)
Review of Penelope Buckley, The Alexiad of Anna Komnene: Artistic Strategy in the Making of a Myth, Cambridge: Cambridge University Press, 2014. xv + 318 pp.